The Comprehensive Systematic Review of Platelet-rich Plasma Injections for Chronic Plantar Fascilitis - Ayub Quisa; Zakiul Ifkar Hamsi; Frederich Gabriel Xaverius Butar Butar; Herfandi Dimas Anugrah (International Medical Journal Corp. Ltd, 2026)
Introduction: Chronic plantar fasciitis (PF) often fails conservative treatment. Corticosteroid (CS) injections provide rapid but temporary relief, while platelet-rich plasma (PRP) offers a regenerative approach. This systematic review compares the efficacy and safety of PRP versus other treatments for chronic PF. Methods: We systematically reviewed randomized controlled trials comparing PRP injections to any control for chronic PF (symptoms ≥3 months). Outcomes included pain (VAS), function (AOFAS), imaging changes, and adverse events. Results: From RCTs (>5,000 patients), and primary studies, a consistent temporal pattern emerged: CS provided faster pain relief at 2–6 weeks, but PRP demonstrated superior and sustained improvements from 3 to 24 months. Key significant positive findings include: at 6 months, PRP was superior to CS for pain (VAS 3.71 vs. 5.40, p<0.0001) (26) and at 24 months for function (AOFAS 92 vs. 56, p=0.001) (4). Meta-analyses confirmed PRP superiority at 3 and 6 months (p=0.01–0.02) (11). PRP produced greater plantar fascia thickness reduction (3.53 vs. 4.58 mm, p<0.001) (45). The safety profile markedly favored PRP (only temporary post-injection pain) versus CS (skin depigmentation, fat pad atrophy, infection) (23). PRP was comparable to surgery with faster recovery (14,15) and superior to extracorporeal shockwave therapy at 90 days (12), dry needling (62), and botulinum toxin (68). Discussion: PRP’s delayed but durable effect aligns with its regenerative mechanism (growth factor-mediated tissue remodeling), whereas CS provides only temporary anti-inflammatory suppression. Conclusion: For chronic PF, PRP provides superior, longer-lasting pain relief and functional improvement compared to CS, with an excellent safety profile. PRP should be preferred over repeated CS and considered before surgery.